Modeling and software for forecasting electricity consumption by airport facilities - Соколова, Наталія Петрівна (Eastern-European Journal of Enterprise Technologies, 2014)
The article proposes software for modeling the forecasting of electricity consumption at an airport, taking into account the specifics of its equipment. This will make it possible to identify in the dynamics and visually represent objects with abnormal power consumption, to effectively forecast power consumption by individual objects and the entire complex as a whole at the stage of reconstruction and construction of a new one.